A Study on Students Acquisition of IT Knowledge and Its Implication on M-Learning - A. Balavivekanandhan; S. Arulchelvan (The Scientific World Journal)
The boom in mobile technology has seen a dramatic rise in its usage. This has led to usage of mobiles even in the academic context for further learning. Although the advantages of m-learning (mobile learning) are visible, studies are required to address the aspects that shape its virtual expectations. The acceptance of mobile technology relies mostly on how the students feel about mobile technology fitting into their requirements. Yet, in spite of the significance in the potential of m-learning, research studies have only inadequate data to identify the factors that influence their decision to adapt the mobile technology for the purpose of learning. To deal with this space, the present study was undertaken to correlate the IT skills of students with their impact on their acceptance of m-learning. The research study found that the perceived usability along with the usefulness of m-learning impacts the association between IT expertise and the objective of learners’ acceptance of m-learning. A survey of 892 students from Engineering, Arts, and Science Colleges found that IT skills influence student’s acquisition of m-learning technology. Specialized and advanced skills in mobile technology along with basic skills play a significant role in influencing a student to accept m-learning. But no specific substantiation has been established to support the statement that highly developed IT skills have influenced the students to accept m-learning.